2015
DOI: 10.1158/2159-8290.cd-14-0849
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A Deficiency Impairs the DNA Damage Checkpoint and Sensitizes Cells to PARP Inhibitors

Abstract: ARID1A, a chromatin remodeler of the SWI/SNF family, is a recently identified tumor suppressor that is mutated in a broad spectrum of human cancers. Thus, it is of fundamental clinical importance to understand its molecular functions and determine whether ARID1A deficiency can be exploited therapeutically. In this manuscript, we report a key function of ARID1A in regulating the DNA damage checkpoint. ARID1A is recruited to DNA double strand breaks (DSBs) via its interaction with the upstream DNA damage checkpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
381
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(411 citation statements)
references
References 60 publications
22
381
3
5
Order By: Relevance
“…these complexes rearrange the distribution of nucleosomes, thereby modifying chromatin configuration and DNA accessibility to cellular machineries involved in transcription, DNA replication, DNA methylation, and DNA repair (1)(2)(3).…”
mentioning
confidence: 99%
“…these complexes rearrange the distribution of nucleosomes, thereby modifying chromatin configuration and DNA accessibility to cellular machineries involved in transcription, DNA replication, DNA methylation, and DNA repair (1)(2)(3).…”
mentioning
confidence: 99%
“…To gain insight into the mechanisms by which Arid1a loss promotes tumorigenesis in the Chaos3 model, we considered data showing that Arid1a is required for efficient functioning of the DNA damage response (DDR), specifically the G2/M cell-cycle checkpoint that helps suppress genomic instability (GIN) and tumorigenesis (Lobrich and Jeggo 2007;Shen et al 2015) . Since Chaos3 cells have chronic replication stress and GIN (Shima et al 2007;Kawabata et al 2011;Bai et al 2016), it is possible that a loss or reduction of ARID1A in a cell allows escape from DDR-mediated growth arrest or apoptosis, thus promoting carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Some research suggested that ARID1A-mutated cancer may also be treated by targeting residual SWI/SNF activity, the PI3K/AKT pathway, the tumor immunological microenvironment, stabilizing wild-type p53 and by targeting the DNA damage response [47]. Recently it has been found that mutated ARID1A also associated with defects in DNA repair [48]. Such mutations can be another possible target of PARPi to treat cancer.…”
Section: Other Important Genesmentioning
confidence: 99%